Rainfall Estimation with Convective Stratiform Technique (CST) Model - Andi Ihwan; Muliadi Muliadi; Muh. Ishak Jumarang (Jurnal Info Sains : Informatika dan Sains, 2023)
Pontianak City is geographically located on the equator. Based on its location, the atmospheric dynamics in this region fluctuate greatly, the equatorial region throughout the year is exposed to solar radiation so that the potential for convective clouds is very high. This research aims to estimate rainfall based on the characteristics of convective and stratiform rain during extreme weather that causes flooding in Pontianak City. The data used is HIMAWARI 8 satellite image data with a duration of December 22-23, 2023. The method used is Convective Stratiform Technique (CST). The results showed that the atmospheric dynamics on December 22 and 23, 2023 were very high, this was characterized by the formation of high clouds with very low cloud top temperatures below -70°C around Pontianak City. Then the estimation of rainfall based on the CST model can be done during heavy rains that cause flooding in Pontianak City. The model rainfall value overestimates the observation data, on December 22 the difference is very large, while on December 23 the model rainfall is able to approach the obeservation rainfall with a very small difference of 1.2 mm.